2021
DOI: 10.1136/bmjopen-2021-051698
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of trial participants and site staff of participating in and running a large randomised trial within fertility (the endometrial scratch trial): a qualitative interview study

Abstract: ObjectivesTo explore the experiences of endometrial scratch (ES) trial participants and site staff of trial recruitment and participation, in order to improve the experience of participants in future trials.DesignQualitative study of a subset of participants in the ES randomised controlled trial and a subset of trial site staff.SettingA purposeful sample of 9 of the 16 UK Fertility Units that participated in the trial.ParticipantsA purposeful sample of 27 trial participants and 7 site staff.ResultsParticipants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several studies have shown that patients usually hope to join the intervention group when agreeing to participate in a RCT. 20,21 This was also the case in this study, and some women expressed disappointment at not being randomly chosen to join the group they wished for.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have shown that patients usually hope to join the intervention group when agreeing to participate in a RCT. 20,21 This was also the case in this study, and some women expressed disappointment at not being randomly chosen to join the group they wished for.…”
Section: Discussionmentioning
confidence: 74%
“…A study by Chatters et al found that participants often had positive preconceptions regarding the effect of the intervention treatment. They also found that patients randomized for the control group felt disappointed and struggled to understand the need for a control arm in the study [ 11 ]. This indicates that the outcome of the randomization can play an important role in the participants’ decision to continue participation in a trial.…”
Section: Discussionmentioning
confidence: 99%
“…Chatters et al studied the experience of both participating in and running a randomized trial with patient in fertility treatment using qualitative interview with both staff and study participants. They found that study participants had positive preconceptions regarding the effect of the experimental treatment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%